Toward a division of metropolitan labour: An empirical analysis of the metropolitan area of Barcelona - Elena Giraldez Pidal (European Regional Science Association (ERSA), 1998)
The economic globalization, firm?s internationalization and the territorial decentralization of the productive process to increase competitivity via prices is producing not only a new process of international labor division between developed countries that overcome the previous divisions between North and South if not also a division of employment inside big metropolitan areas in developed countries. A divisor process of employment that we can call ?metropolitan division of labor?. This metropolitan regions, old nucleus of regional development it transforms in a complex model which interrelations are necessary analyze to develop, from the public territorial institutions, the adequate strategies. The aim of this paper is analyze the model of metropolitan division of labor in the Metropolitan Area of Barcelona.
Keywords: 330